Implementasi Gaya Kepemimpinan Demokratis Kepala Sekolah untuk Meningkatkan Kinerja Guru di SMA Negeri 1 Wonogiri - Ridho Robani; Triono Ali Mustofa (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
Leadership is key to educational success. Principals with the right leadership can lead schools towards improving services and quality and improving teacher performance at work. The purpose of this study is none other than to identify the democratic leadership style used by the head of SMA Negeri 1 Wonogiri in improving the performance or competence of teachers in teaching. Teacher performance is the result and achievement of teachers in providing good learning to their students, and one of the components that determine the performance of the school itself. This research is a qualitative research, the process is with data collected through interview methods and review of several journals. As a result of the research, the Head of SMA Negeri 1 Wonogiri uses a democratic leadership style that is able to strengthen and maintain the bond between the principal and the teachers and can solve a problem together and the Principal provides freedom for teachers to develop their abilities in various activities to improve teacher performance at SMA Negeri 1 Wonogiri. Further data found that the productivity or performance of teachers at SMA Negeri 1 Wonogori is fairly good. There are 2 ways to assess teacher performance at SMA Negeri 1 Wonogiri, namely using the independent learning platform and e-performance from BKN.